The Dutch Indies Colonial Government System In Onderafdeling Bonthain 1905-1942 - Mesoute Grampell (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
This study aims to determine (i) the transition process from the traditional government system to the colonial government system. (ii) the colonial government administration system, (iii) the influence of the colonial government system on politics and economic activity in Onder Afdeling Bonthain 1905-1942. This study uses a qualitative approach that focuses on historical methods, through the stages of: heuristics, criticism, interpretation, and historiography to find and describe and interpret using data collection techniques through literature and archival reviews. The results of this study indicate that (i) there has been a transition from the traditional government system where the basics of implementing traditional government/kakaraengang are based on customs and royal law. Besides that, With the arrival of the Dutch Colonial, Ada' Sampulo Ruwa officially became Adatregentschapraad as a financial management institution for the local government. (ii) the administrative system developed by the colonial government was fully aimed at supporting the growing paternalistic pattern which had inspired the bureaucratic system in the empire era which was based on the 1922 decentralization law. (iii) the influence of the colonial government system on politics and economic activity in Onderafdeling Bonthain resulted in a process of structural transformation from traditional political and economic structures towards colonial and modern political and economic structures.